2014
DOI: 10.1186/1752-1947-8-402
|View full text |Cite
|
Sign up to set email alerts
|

Septic shock due to Aeromonas hydrophila bacteremia in a patient with alcoholic liver cirrhosis: a case report

Abstract: IntroductionAeromonas hydrophila sometimes causes bacteremia, which can be fatal in compromised patients, such as those with liver cirrhosis. We present a case of septic shock due to Aeromonas hydrophila bacteremia in a patient with liver cirrhosis, which was successfully treated with rapid resuscitation and critical care.Case presentationA 71-year-old Japanese man with liver cirrhosis was transported to our emergency center by ambulance after presenting with gait difficulties and fever. On arrival, he exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…Although intensive treatments including veno-arterial extracorporeal membrane oxygenation, T A B L E 2 Mortality analysis of patients with Aeromonas hydrophila isolation polymyxin B hemoperfusion, or cytokine-absorbing hemofiltration have been reported as successful for patients with A hydrophila sepsis, the effect might be limited. 17,18 Our mortality analysis showed that blood loss > 1000 mL might be a risk factor for mortality in patients with A hydrophila infection. However, massive blood loss has long been recognized as a risk factor for SSI.…”
Section: Discussionmentioning
confidence: 89%
“…Although intensive treatments including veno-arterial extracorporeal membrane oxygenation, T A B L E 2 Mortality analysis of patients with Aeromonas hydrophila isolation polymyxin B hemoperfusion, or cytokine-absorbing hemofiltration have been reported as successful for patients with A hydrophila sepsis, the effect might be limited. 17,18 Our mortality analysis showed that blood loss > 1000 mL might be a risk factor for mortality in patients with A hydrophila infection. However, massive blood loss has long been recognized as a risk factor for SSI.…”
Section: Discussionmentioning
confidence: 89%
“…The clinical characteristics and prognoses of 25 reported cases of Aeromonas infections in patients with LC in Japan reported from 1992 to 2016 are summarized in Table 1. Among the 25 cases, three were reported in English [4,13,14] and the remaining 22 in Japanese [9,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The age at diagnosis of Aeromonas infection ranged between 40 and 78 years, and 19 patients were male and five were female with one case unknown.…”
Section: Case Reports Of Aeromonas Infections In Japanmentioning
confidence: 99%
“…The age at diagnosis of Aeromonas infection ranged between 40 and 78 years, and 19 patients were male and five were female with one case unknown. The etiology of LC was as follows: hepatitis C virus (HCV) infection in six cases [13,21,22,25,29], hepatitis B virus infection in six [9,11,16,26,27,30], alcohol-related in nine [4,14,15,17,20,21,23,28,31] HCV infection plus alcoholrelated in one [22], and unknown in three [18,19,24]. The Child-Pugh classification of underlying liver dysfunction was as follows; Child C in nine, Child B in one, and unknown in 15 cases.…”
Section: Case Reports Of Aeromonas Infections In Japanmentioning
confidence: 99%
“…infecciones son causadas por Escherichia coli, Klebsiella spp., Enterobacter spp. y P. aeruginosa 23 . En el reporte presentado, el origen de la sepsis fue una bacteremia descartando previamente los otros focos más frecuentes.…”
Section: Presentación De Caso Clínicounclassified
“…En pacientes cirróticos, lo anterior se ha relacionado con la presencia de translocación bacteriana por alteración de la barrera intestinal producto del edema, congestión e hipoxia local 26,27 . En el caso presentado, no fue posible identificar heridas, infecciones en piel o trauma previo al inicio del cuadro clínico, por lo que se consideró como fuente más probable de transmisión la vía oral como se ha reportado en otros casos similares 23,27 .…”
Section: Presentación De Caso Clínicounclassified